Evaluation of the implementation of educational assessment standards at Madrasah Tsanawiyah Modern Islamic Boarding School - Nurul Ngarifillaili; Badrun Kartowagiran; Umwari Yvette (REID (Research and Evaluation in Education), 2021)
This study aims to collect, analyze, and present evaluation results and assess them by comparing the evaluation indicators. The evaluation focuses on achieving and implementing seven components of the Educational Assessment Standard in Islamic middle school (Madrasah Tsanawiyah or MTs) of modern Islamic boarding schools (pesantren) in the Kebumen Regency. The study employed a descriptive quantitative approach. The evaluation model was the discrepancy evaluation model. The study subjects were 227 students of grade VIII class 2020/2021. Data collection was performed using a questionnaire and brief interviews. The study result shows that 70.55% of students stated the assessment comprises three aspects, i.e., knowledge, attitude, and skills. The assessment principles of valid, objective, fair, integrated, open, thorough and sustainable, systematic, based on criteria, and accountable have been implemented well. About 67.82% of students assert that all principles have been reflected during assessment by educators and education units. As much as 72.35% of students explained that the assessment had utilized an appropriate form to measure students’ competency achievement. The assessment of MTs in modern pesantren in Kebumen Regency used an instrument following the regulation, where 74.82% of students revealed that the study instrument had followed the empirical validity requirement.